2016
DOI: 10.1007/s00259-016-3312-x
|View full text |Cite
|
Sign up to set email alerts
|

[123]FP-CIT SPECT scans initially rated as normal became abnormal over time in patients with probable dementia with Lewy bodies

Abstract: PurposeDecreased striatal dopamine transporter (DAT) binding on SPECT imaging is a strong biomarker for the diagnosis of dementia with Lewy bodies (DLB). There is still a lot of uncertainty about patients meeting the clinical criteria for probable DLB who have a normal DAT SPECT scan (DLB/S−). The aim of this study was to describe the clinical and imaging follow-up in these patients, and compare them to DLB patients with abnormal baseline scans (DLB/S+).MethodsDLB patients who underwent DAT imaging ([123I]FP-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
67
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 28 publications
6
67
0
1
Order By: Relevance
“…In 2 of these cases, 18 F‐FDG‐PET was performed before DAT‐SPECT. It has been shown that some DLB patients may initially have unremarkable DAT scans 30. It is possible that RBD subjects with significant PDRP expression but normal DAT binding will eventually develop DLB.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 of these cases, 18 F‐FDG‐PET was performed before DAT‐SPECT. It has been shown that some DLB patients may initially have unremarkable DAT scans 30. It is possible that RBD subjects with significant PDRP expression but normal DAT binding will eventually develop DLB.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 88 % sensitivity found by Walker et al suggests that one in eight DLB patients with confirmed DLB pathology at autopsy might have a normal 123 I-ioflupane SPECT scan. The patient with a normal scan actually had an asymmetric presentation with right-sided parkinsonism resembling a corticobasal syndrome, with abnormal posterior left putamen uptake on visual analysis but normal average counts between the two putamina (the index considered in the paper).…”
mentioning
confidence: 86%
“…The demonstration of nigrostriatal dopaminergic impairment by SPECT or PET was included in the diagnostic criteria published in 2005 merely as a supportive feature [3]. Still a head-to-head comparison between 123 Iioflupane SPECT and neuropathology was needed. This was performed by Walker et al [4] who found a specificity of 100 % and a sensitivity of 88 % with semiquantitative analysis of the posterior putamen.…”
mentioning
confidence: 99%
See 2 more Smart Citations